(untitled) (Damascus University Journal of agriculture sciences, 2021)
Potato leafroll virus (genus Polerovirus,family Luteoviridaae, PLRV) is one of important viruses that infect potato crop in Syria and transmitted by aphids in a persistent manner. Partially purified viral preparation was obtained from local Syrian PLRV isolate (SP 25-12) from Sponta cultivar in potato fields in Khan-Alsheih in Damascus Countryside during survey 2012. The virus was semi-purified from infected or inoculated leaves of Physalis floridana by using sodium phosphate buffer 0.01 M and by clarifying extracts, precipitation of virus with polyethylene glycol (PEG) and differential centrifugation. The efficiency of virus transmission was also tested in an experiment by using several dilutions of partially-purified PLRV isolate and conducted by green peaches aphids Myzus persicae through parafilm membranes covered with a thin layer of sucrose solution 20%. Results of ELISA showed the success of aphids in transmitting the virus through membranes on P. floridana, and the infection was assessed through symptom expression of chlorosis and veins clearing on the leaves after 3-4 weeks of infection. The transmission rate of PLRV ranged 20 - 70%. This is the first test of local PLRV isolate and transmission of M. persicae virus through parafilm membranes.